2016
DOI: 10.1080/0284186x.2016.1250946
|View full text |Cite
|
Sign up to set email alerts
|

Determinants in the place of death for people with different cancer types: a national population-based study

Abstract: Background: Place of death has for the past decade increasingly come to be regarded as a robust indicator of how palliative care is organized and provided, and is also recognized as an important factor for well being at the end of life. Variations in place of cancer deaths have previously been reported in the context of country-specific healthcare organization, but without differentiating between cancer types and national regional variations. Our aim was to examine, at a population level, where people with can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Fourteen papers specifically stated, that they only included adult patients. 21,2830,35,39,40,42,46,47,50,51,53,54…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen papers specifically stated, that they only included adult patients. 21,2830,35,39,40,42,46,47,50,51,53,54…”
Section: Resultsmentioning
confidence: 99%
“…22,24 However, studies from other continents found the opposite, namely, that a higher education level was associated with dying at home (ORs between 1.17 and 1.96). 25,36,50,54…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations